Structural properties of the alluaudite-type materials Ag2–xNaxMn3(VO4)3 (x=0.62 and 1.85) - Hamdi Ben Yahia (14579467) (2019)
The new members of the Ag2−xNaxMn3(VO4)3 (0 ≤ x ≤ 2) solid solution were synthesized by a solid-state reaction route. The crystal structures of Ag1.38Na0.62Mn3(VO4)3 (x = 0.62) and Ag0.15Na1.85Mn3(VO4)3 (x = 1.85) were solved using single crystal X-ray diffraction. These phases crystallize with a monoclinic symmetry (space group C2/c), and their structures are new members of the well-known alluaudite family. In both compounds, the Ag+/Na+, Mn2+/Mn3+ and V5+ cations are eight-, six-, and four-coordinated to oxygen atoms, respectively. All the atoms are perfectly ordered except for the Ag and Na atoms which are statistically disordered over a 4b and a 4e atomic position. This single-crystal structural study confirms the existence of a full solid solution Ag2−xNaxMn3(VO4)3 (0 ≤ x ≤ 1.85). Other information Published in: Zeitschrift für Naturforschung B License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1515/znb-2019-0116